PENGGUNAAN MEDIA VIDEO TERHADAP KEBERHASILAN MENYUSUI DI KELURAHAN PACCERAKKANG - Chaerunnimah Chaerunnimah; Aswita Amir; Retno Sri Lestari; Zhulfitriana Anwar (Media Gizi Pangan, 2023)
Exclusive breast milk can reduce infant morbidity and mortality. Exclusive breastfeeding coverage based basic health research in indonesia 2018 data has only reached 37.3%. One of the factors that influences breastfeeding is the mother's success in breastfeeding. Media use influences the success of health education. The aim of this research was to determine the effect of using video media on breastfeeding success and the type of breastfeeding (completely breast milk or a combination of breast milk and formula milk). This type of research is pre-experimental with a posttest only design. In this design, the data collected is the effect of education after the intervention. Population of breastfeeding mothers in the Paccerakkang Community Health Center working area. The research sample was breastfeeding mothers with babies 0-1 months old and willing to be given breastfeeding education obtained using the purposive sampling method. The research results showed that 81.3% of mothers from the intervention group were successful and able to breastfeed their babies well and in the control group 100% of mothers were successful and able to breastfeed their babies well. The Mann Whitney test results showed p=0.105 (p>0.05). The conclusion of this study is that there is no significant difference in the success and provision of breast milk in the intervention group and the control group.